Nasalance scores for typical Irish English-speaking adults. (December 2013) - Lee, Alice; Browne, Una
Abstract: The aim was to establish normative nasalance values for Irish English-speaking adults. Thirty men and 30 women with normal resonance read aloud 16 sentences from the Irish nasality assessment protocol, the Zoo passage, and the Rainbow passage. The speech samples were recorded using the Nasometer II 6400. Results of a mixed between–within subjects ANOVA indicated no significant gender effect on nasalance scores. The speakers showed significantly higher nasalance scores for high-pressure consonant sentences than low-pressure consonant sentences, and for the Rainbow passage than total test sentences. There was no significant difference between high-pressure consonant sentences and the Zoo passage. Compared to previous studies, the Irish young adults had lower nasalance scores than Irish children and than young adults with North American dialects.